2000
DOI: 10.2739/kurumemedj.47.173
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Surgery in a Patient with Myasthenia Gravis.

Abstract: A 73-year-old man with myasthenia gravis required quadruple coronary artery bypass grafting due to triple-vessel disease. Anesthetic management was performed with general anesthesia using a reduced dose of muscle relaxant with the aid of a neuromuscular transmission monitor. He was extubated 14 hrs after surgery without difficulty under this monitor. His postoperative course was uneventful. A patient with myasthenia gravis who required coronary artery bypass surgery was successfully performed by the deliberate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…It confirms previous findings (Asai et al, 2004;Hayashida et al, 2000) that such patients may safely undergo CPB for CABG with cisatracurium as a muscle relaxant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It confirms previous findings (Asai et al, 2004;Hayashida et al, 2000) that such patients may safely undergo CPB for CABG with cisatracurium as a muscle relaxant.…”
Section: Discussionsupporting
confidence: 89%
“…It was shown that increased anti-AChR antibody levels were associated with increased sensitivity to vecuronium (Nilsson & Meretoja, 1990), but no relation between anti-AChR antibody levels and atracurium requirements was found (Hayashida et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…MG patients, particularly those undergoing major surgery, require special individual preoperative management, appropriate selection and administration of anesthesia, and close monitoring postoperatively [Rudzka-Nowak 2011]. Particularly in patients undergoing trans-sternal surgical procedures such as thymectomy and cardiac surgery, the choice of anesthetic drug and the choice of technique require special consideration, because postoperative pain interferes with pulmonary function, which may already be limited by the disease [Hayashida 2000].…”
Section: Discussionmentioning
confidence: 99%
“…There have been very few reports describing perioperative anesthetic management in MG patients undergoing cardiac surgery [Hayashida 2000;Narin 2009;Ishimura 1998;Asai 2004;Haroun-Bizri 2003]. Some anesthesiologists prefer to avoid muscle relaxants, and use potent inhaled agents both for facilitating tracheal intubation and providing surgical relaxation, whereas some prefer a total intravenous anesthesia [Narin 2009].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation